2012
DOI: 10.5603/fhc.2012.0079
|View full text |Cite
|
Sign up to set email alerts
|

Pulpo-dentin complex response after direct capping with self-etch adhesive systems

Abstract: Abstract:The purpose of the present study was to evaluate morphologically the response of feline teeth pulp to direct pulp capping with two different self-etch adhesive systems. Twenty-four cavities in feline teeth were mechanically exposed and assigned to one of two experimental groups: AdheSE + Tetric Ceram (the ASE group), or Adper Prompt L-Pop + Filtek Supreme (the APLP group). There was also a control group Dycal Ca(OH) 2 liner + Amalgam (the CH group eight teeth), and six teeth were used as an intact con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[35] However, it has been suggested that data obtained from animal teeth should not be directly extrapolated to human clinical conditions. [25,36] Thus, in this study, we chose to examine human teeth.…”
Section: Discussionmentioning
confidence: 99%
“…[35] However, it has been suggested that data obtained from animal teeth should not be directly extrapolated to human clinical conditions. [25,36] Thus, in this study, we chose to examine human teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Especially after cervical restorations, prolonged contact of Bis-GMA with gingival tissues may cause lichenoid reactions or irritations in the oral mucosa. 29 In a study by Nowicka et al 30 , the response of the pulpdentin complex was analyzed after direct pulp capping treatment using self-etch adhesive systems. In most of the specimens, pulpal reaction and lack of dentin bridge formation occurred with tissue disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse reactions to dental materials occur in patients and dental personnel [1••]. Local reactions take place at the exposure site, e.g., dental pulp and pulp inflammation after pulp capping with adhesives and resin-based composites has been described [2][3][4][5], which was related to substances released from the applied materials. Also, inhibition of biomineralization after pulp capping with adhesives was observed [6] and can also be related to eluted substances from dental materials such as acrylic monomers [7, 8••].…”
Section: Introductionmentioning
confidence: 99%